Developing MIS for National Innovation Foundation : choosing process, product, & vendor - Verma, Sanjay, (SAGE Knowledge. Cases., 2016)
National Innovation Foundation (NIF) was a partner organization of the Honey Bee Network (HBN) which was a networked organization of individuals, innovators, farmers, scholars, academicians, policy makers, entrepreneurs and non-governmental organizations (NGOs). The HBN worked to create a network of grassroot innovators and acknowledged them by protecting their IPR. NIF was an autonomous body of the Department of Science and Technology (DST), Government of India, which provided institutional support to grassroot innovators, and facilitated the diffusion of traditional knowledge through various channels. NIF also handled filing patents and licensing of grassroot technology.NIF did not have any integrated system that could track the status of their various activities. Different softwares managed different modules and these applications did not interact with each other. Data resided in physical files and progress was tracked manually. NIF wanted to implement Enterprise-wide ERP software that could provide a comprehensive view of the organization. In this regard, the organization appointed MindTree Ltd. to do feasibility analysis and provide a Software Requirement Specification (SRS) document to NIF. The SRS document along with an overview of expected deliverables was shared with potential vendors and four vendors were finalized based on convenience. The project team at NIF was examining proposals from vendors and was also considering other cost effective options which would achieve their objective. The project team had to take decisions on a number of crucial aspects like deciding which software development methodology to adopt and what approach to follow which would suit the unique requirements of the organization. NIF was a dynamic organization and their requirements kept changing. How to determine a pricing policy was another major concern for the project team.